2006
DOI: 10.1159/000097866
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Flow Velocity after Stenting of Renal Arteries Is Associated with Decreased Renal Function

Abstract: Background: Atherosclerotic renal artery stenosis (RAS) is frequently treated by angioplasty and stent placement. Duplex sonography is an established noninvasive technique for patient follow-up. There is lack of evidence that routine monitoring of asymptomatic patients with stable blood pressure is needed. Methods: Renal duplex sonography was performed in 64 patients who had received percutaneous angioplasty and stenting of an atherosclerotic RAS. Duplex sonographic diagnosis was made by a combination of direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Several studies [44,45] have shown good technical success rates immediately after the procedure, but restenosis rates approximately from 2% to 36% at 6e12 months follow-up. Assessment of restenosis of RA stents is important in the clinical management of individual patients to determine the long-term benefits of the procedure.…”
Section: Evaluation In Assessing Restenosis Of Renal Artery Stentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [44,45] have shown good technical success rates immediately after the procedure, but restenosis rates approximately from 2% to 36% at 6e12 months follow-up. Assessment of restenosis of RA stents is important in the clinical management of individual patients to determine the long-term benefits of the procedure.…”
Section: Evaluation In Assessing Restenosis Of Renal Artery Stentsmentioning
confidence: 99%
“…8a,b). Girndt et al [44] reported a sensitivity and specificity of 100% and 74%, respectively, using the published threshold value of in-stent PSV >180 cm/s. If the published threshold value of RAR >3.5 Fig.…”
Section: Evaluation In Assessing Restenosis Of Renal Artery Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-arterial stenting is rapidly becoming the modality of choice for the management of occlusive, degenerative and aneurysmal disease. As the use of endovascular stents has increased, the complications associated with their use have become manifest and include restenosis (Girndt et al 2007), proximal neck dilation (Rodway et al 2008), stent migration and endoleak (Bush et al 2006). These complications can be at least partially attributed to the physical and mechanical properties of the endovascular stents.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Girndt et al have noted that a decrease in renal function over time is significantly higher in patients with flow enhancement (a flow velocity of Ͼ2.0 m/s) and that there is a high rate of in-stent restenosis associated with enhanced loss of renal function. 24 We did see a higher rate of restenosis in the group that suffered parenchymal loss. A recent study of magnetic resonance (MR)-based renal artery flow measurements and renal parenchymal volume has demonstrated that normal kidney volume results in a high sensitivity (91%) but a low specificity (33%) for a response to renal intervention defined as a reduction in diastolic blood pressure Ͼ15% or a reduction in serum creatinine Ͼ 20%.…”
Section: Discussionmentioning
confidence: 64%